Predictors for the severity of bronchial hyperreactivity in childhood asthma - AKKOÇ, TUNÇ (AMER THORACIC SOC, 2001)
Bronchial hyperreactivity (BHR) is a common characteristic of asthma and is shown to be a risk factor in the development and outcome of asthma. In this study, we aimed to assess the risk factors at referral for the severity of BHR, which was determined at the end of a mean of 3 yr of follow-up in 98 children with asthma (mean (+/- SD) age, 11.0 (+/- 3.4) yr, male/female = 50/48]. We also evaluated the cross-sectional risk factors for the severity of BHR in the observed children. Information on risk factors at referral was collected from the computer records of the patients followed by an end-of-study visit. Lung function, skin-prick, and bronchial provocation tests were done and total serum IgE level was measured on this visit. The relationship between BHR and risk factors was investigated by multiple linear regression analysis. A lower level of FEV1% at referral was found to be an important predictor of more severe BHR at the end of the follow-up. None of the other risk factors evaluated predicted the severity of current BHR. We concluded that decreased lung function at referral is associated with a more severe BHR determined at the end of a 3-yr follow-up in children with asthma.
Keywords: asthma; bronchial hyperreactivity; children; FEV1; AIRWAY HYPERRESPONSIVENESS; RISK-FACTORS; RESPONSIVENESS; IGE; INFLAMMATION; POPULATION; ADULTHOOD; SYMPTOMS; MODEL